Genomics and proteomics: one further step - Aldecoa Bedoya, Franklin (2024)
The development of genomics and proteomics depends on fundamental discoveries that resulted in new paradigms, theories and technologies, that have drastically changed the focus of medical sciences. The discovery of the structure of DNA and the basic functions of replication, transcription and translation, associated to the manipulation of cellular genetic material through restriction enzymes, ligases, polymerases, nucleotide base sequences, etc., lead us to genetic engineering, the disclosure of the human genome, the creation of new tools for the study of diseases and diagnosis, such as PCR (Polymerase Chain Reaction), microarray technology, and the better understanding of the behavior of our organism in relation to medication (pharmacogenomics). Now we have a greater challenge: to improve our understanding of the behavior of proteins as basic elements, the machinery through which DNA generates life. These new concepts carry new responsibilities, bring up ethical and moral problems and the need for appropriate legislation for their development.